2013
DOI: 10.4161/cc.26221
|View full text |Cite
|
Sign up to set email alerts
|

PDIP38 is translocated to the spliceosomes/nuclear speckles in response to UV-induced DNA damage and is required for UV-induced alternative splicing of MDM2

Abstract: (2013) PDIP38 is translocated to the spliceosomes/nuclear speckles in response to UV-induced DNA damage and is required for UVinduced alternative splicing of MDM2, Cell Cycle, 12:19,[3373][3374][3375][3376][3377][3378][3379][3380][3381][3382]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 59 publications
0
34
2
Order By: Relevance
“…Using the technique of UV exposure through UV-opaque polycarbonate filters with 5 or 10 μm pores to create local areas of irradiation [84], it was observed that PDIP38 was not recruited to these DNA damage foci, in contrast to Pol η and PCNA [199]. This finding does not negate the proposal that PDIP38 is involved in Pol η recruitment [190], since the mechanism is unknown and might involve a transient association of PDIP38 to DNA damage sites.…”
Section: Pdip38 Responds To Genotoxic and Transcriptional Stress By Tcontrasting
confidence: 42%
See 1 more Smart Citation
“…Using the technique of UV exposure through UV-opaque polycarbonate filters with 5 or 10 μm pores to create local areas of irradiation [84], it was observed that PDIP38 was not recruited to these DNA damage foci, in contrast to Pol η and PCNA [199]. This finding does not negate the proposal that PDIP38 is involved in Pol η recruitment [190], since the mechanism is unknown and might involve a transient association of PDIP38 to DNA damage sites.…”
Section: Pdip38 Responds To Genotoxic and Transcriptional Stress By Tcontrasting
confidence: 42%
“…Thus, the translocation of PDIP38 to the spliceosomes is a novel DNA damage response [199]. In addition to genotoxic stress, transcriptional stress induced by α-amanitin also led to translocation of PDIP38 to the nuclear speckles [199]. Interestingly, the human DNA glycosylase hOGG1 is also translocated to the nuclear speckles under the influence of UVA [201].…”
Section: Pdip38 Responds To Genotoxic and Transcriptional Stress By Tmentioning
confidence: 99%
“…Poldip2 is fairly ubiquitously expressed, having been reported in aorta, 3, 4 lung, 3 kidney, 3, 5, 6 heart 7 and thyroid, 8 as well as many cell types including mouse aortic smooth muscle cells, 9 astrocytes, 10 vascular smooth muscle cells (VSMC), 3, 11 brain endothelial cells, 12 epithelial cells, 12 HeLa, 1, 12-15 fibroblasts, 2, 13, 16, 17 kidney fibroblasts, 18 myoblasts, 19 human umbilical vein endothelial cells, 20 human embryonic kidney cells 293 (HEK 293), 13 MRC5 cells, 21, 22 and cortical neurons. 23 There is also evidence of Poldip2 expression in human breast cancer, 24 human breast adenocarcinoma cells 13 and human lung adenocarcinoma cells.…”
Section: Tissue Expressionmentioning
confidence: 99%
“…Thus, Poldip2 is necessary for vascular integrity and function. 17 However, in addition to regulating Nox4, Poldip2 has a number of other reported functions, including roles in organizing the mitotic spindle, DNA repair, and cellular adhesion 18 19-21 . Many of these processes can potentially contribute to collateralogenesis.…”
Section: Introductionmentioning
confidence: 99%